The Art of Living Together: The Work of Caiozzama, Delight Lab, and LASTESIS during Chile’s 2019-2020 Protests - Ashley, Jennifer (Anthropologica)

(untitled) (University of Victoria, 2022)
On 18 October 2019, a protest over an increase in metro fares in Santiago, Chile transformed into a nationwide uprising against inequality. As the protests evolved, it became clear that the discontent stemmed not only from the economic effects of the neoliberal model put into place during the Pinochet dictatorship (1973 to 1990), but also from the modes of relationality that it had engendered. The messages that protesters scrawled on the walls of the city insisted on the need for more empathy, respect, and dignity. Chilean artists responded by creating works that framed these individual grievances as collective experiences of a crisis in what in Spanish is called convivencia, or the art of living together. In this piece, I review the paste-up graffiti of Caiozzama, the visual mappings of Delight Lab, and the feminist performances of LASTESIS to highlight how these artists supported protesters’ call for dignity and a new mode of convivencia.